Prevalence of pterygium and pinguecula and their risk factors: Tehran Geriatric Eye Study - Alireza Hashemi; Mohamadreza Aghamirsalim; Hassan Hashemi; Pooneh Malekifar; Mehdi Khabazkhoob (International Journal of Ophthalmology)
AIM: To explore the prevalence of pterygium and pinguecula and their risk factors. METHODS: This population-based cross-sectional study was conducted on geriatric population aged 60 and over in Tehran, Iran from Jan 2019 to Jan 2020. Selected subjects were interviewed and subjected to optometric and ophthalmic examinations. RESULTS: The age and sex standardized prevalence of pterygium and pinguecula was 3.64% [95% confidence interval (CI): 2.94%–4.49%] and 55.57% (95%CI: 52.89%–58.22%), respectively. The prevalence of pterygium was 4.52% (95%CI: 3.5%–5.81%) in men and 2.79% (95%CI: 1.97%–3.94%) in women and the prevalence of pinguecula was 64.56% (95%CI: 60.92%–68.03%) in men and 46.72% (95%CI: 43.74%–49.72%) in women. According to the results of multiple logistic regression, pinguecula had a significant correlation with male sex [odds ratio (OR): 2.21, 95%CI: 1.63–2.99] and education level (OR: 0.52, 95%CI: 0.35-0.77) and pterygium had a significant relationship with male sex (OR: 2.2, 95%CI: 1.38–3.52), socioeconomic status (SES, OR: 0.5, 95%CI: 0.26–0.97), education level (OR: 0.22, 95%CI: 0.08–0.61). CONCLUSION: The prevalence of pinguecula and pterygium in this study are lower than other studies. Sex, SES, and education level are the risk factors of the prevalence of pinguecula and pterygium.